Development of a highly specific enzyme-linked immunosorbent assay for detection of antibodies to Duck Tembusu virus using subviral particles. - Iyarath Putchong; Thaweesak Songserm; Sittinee Kulprasertsri; Shintaro Kobayashi; Preeda Lertwatcharasarakul; Wallaya Phongphaew (PLoS ONE)
Duck Tembusu virus (DTMUV) belongs to the family Flaviviridae and genus Orthoflavivirus. It causes disease in ducks, affecting the nervous system and significantly reducing egg production. The first outbreak of DTMUV in Thailand was reported in 2013, with widespread cases across various regions. However, serological diagnosis of DTMUV is challenging due to antibody cross-reactivity with other flaviviruses. To address this issue, we developed an ELISA based on subviral particles. The cassette encoding the membrane precursor and envelope genes of DTMUV (strain KPS54A61) were cloned into a pCAGGS vector with an OSF-tag and transfected into HEK-293T cells to generate subviral particles. The subviral particles were detected in the supernatant of the transfected cell via immunoblotting using anti-DTMUV E protein and anti-Strep-tag antibodies, which revealed a protein band of approximately 59 kDa. An electron microscopy confirmed the presence of particles approximately 35 nm in diameter. To optimize the SP-based ELISA, checkerboard titration identified the optimal antigen concentration as 70 µg/mL and the optimal serum dilution as 1:100,000. A cut-off value was established for the assay, and testing 300 duck serum samples using the SP-based ELISA identified 41 positive samples (14%) and 259 negative samples (86%). The SP-based ELISA exhibited 100% sensitivity and specificity, achieving a perfect agreement score of 1.0 in comparison with the serum neutralization test. Additionally, specificity testing using antibodies specific to Japanese Encephalitis virus (JEV) revealed no cross-reactivity in the ELISA test. Therefore, the developed SP-based ELISA is highly effective for screening and monitoring DTMUV outbreaks in duck farms, significantly reducing the risk of viral spread and enabling the timely implementation of disease control measures.